POLYMORPHISMS IN THE SUPEROXIDE DISMUTASE-3 GENE ARE ASSOCIATED WITH EMPHYSEMA IN COPD - Sørheim, IC (2010)
Superoxide dismutase-3 (SOD3) is a major extracellular antioxidant enzyme, and previous studies have indicated a possible role of this gene in chronic obstructive pulmonary disease (COPD). We hypothesized that polymorphisms in the SOD3 gene would be associated with COPD and COPD-related phenotypes. We genotyped three SOD3 polymorphisms (rs8192287 (E1), rs8192288 (I1) and rs1799895 (R213G)) in a case-control cohort, with severe COPD cases from the National Emphysema Treatment Trial (NETT, n=389) and smoking controls from the Normative Aging Study (NAS, n=472). We examined whether the SNPs were associated with COPD status, lung function variables, and quantitative CT measurements of emphysema and airway wall thickness. Further, we tried to replicate our initial findings in two family-based studies, the International COPD Genetics Network (ICGN, n=3061) and the Boston Early-Onset COPD Study (EOCOPD, n=949). In NETT COPD cases, the minor alleles of SNPs E1 and I1 were associated with a higher percentage of emphysema (%LAA950) on chest CT scan (p=0.029 and p=0.0058). The association with E1 was replicated in the ICGN family study, where the minor allele was associated with more emphysema (p=0.048). Airway wall thickness was positively associated with the E1 SNP in ICGN; however, this finding was not confirmed in NETT. Quantitative CT data were not available in EOCOPD. The SNPs were not associated with lung function variables or COPD status in any of the populations. In conclusion, polymorphisms in the SOD3 gene were associated with CT emphysema but not COPD susceptibility, highlighting the importance of phenotype definition in COPD genetics studies.